2003
DOI: 10.1007/s00428-003-0817-z
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy and breast cancer: a population-based study

Abstract: The incidence of pregnancy-associated breast cancer, i.e. during pregnancy and lactation, and of pregnancy subsequent to a breast-cancer diagnosis will increase as more women choose childbearing at a later age. Few larger series are published on pregnancy-associated breast cancer. In a population-based study, we evaluated the outcome and prognostic factors in 173 breast-cancer patients. One hundred and twenty-two patients had pregnancy-associated breast cancer (20 coincident with pregnancy and 102 during lacta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(14 citation statements)
references
References 42 publications
1
12
0
1
Order By: Relevance
“…HER-2/neu is synthesized in many embryonic tissues during pregnancy [34], and thus HER-2/neu over-expression was observed in 47.6% of the PABC patients, which is higher than that reported by Middleton (28%) [32], Garcia-Manero (31.6%) [12] and Halaska (33.3%) [17]. The rate of HER-2/neu oncogene over-expression in PABC patients was also higher than that among non-PABC group, which is similar to previously reported studies of 44% versus 28% of the control group [35].…”
Section: Discussionsupporting
confidence: 82%
“…HER-2/neu is synthesized in many embryonic tissues during pregnancy [34], and thus HER-2/neu over-expression was observed in 47.6% of the PABC patients, which is higher than that reported by Middleton (28%) [32], Garcia-Manero (31.6%) [12] and Halaska (33.3%) [17]. The rate of HER-2/neu oncogene over-expression in PABC patients was also higher than that among non-PABC group, which is similar to previously reported studies of 44% versus 28% of the control group [35].…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, compared to non-PABC cases, various studies reported these combined pregnant and early postpartum tumors are marked by reduced estrogen and progesterone receptor positivity [1, 12, 13, 16], as well as higher frequency of Her2 neu positivity but not specifically the triple negative subtype [13, 17]. When early postpartum and pregnant cases were evaluated independently, there was contradictory data reported on the clinicopathologic features of these pregnant and postpartum subsets [12, 13, 1720]. Moreover, a recent PABC publication concluded triple negative tumors were more likely to be diagnosed within two-years postpartum [17].…”
Section: Discussionmentioning
confidence: 99%
“…With latent/preclinical time period being considered, it is likely that more breast cancer cases are pregnancy-associated (58). Recent publications suggest that PABC occurred during 5-year postpartum has worse prognosis comparing to those occurred during pregnancy (33), possibly due to mammary gland involution upon weaning (59); while another study using the one-year postpartum definition found the two groups (pregnancy vs. lactation) very similar (60). In our study, there was only one PABC case diagnosed during pregnancy and we could not examine the two groups separately.…”
Section: Discussionmentioning
confidence: 99%